تقييم الاستجابة الديناميكية لخزانات المياه العالية تحت أحمال الزلازل – دراسة حالة نموذج شائع الاستخدام في الساحل السوري (Latakia University Journal -Engineering Sciences Series, 2018)
تطرق البحث الى الدراسة التحليلية لخزانات المياه العالية ودراسة السلوك الديناميكي اللاخطي لتأثير الفعل المتبادل (سائل –منشأ- تربة ) على استجابتها الديناميكية . حيث تم تطبيق هذه الدراسة على نموذج خزان شائع الاستخدام في الساحل السوري جملته الحاملة من البيتون المسلح بارتفاع 15 م وبطاقة تخزينية 100 م³ . وتمت نمذجة الخزان والجملة الحاملة له والتربة المحيطة بطريقة العناصر المنتهية باستخدام برنامج ABAQUS وقمنا بنمذجة الماء ضمن حوض الخزان وفقا لطريقةGAREANE. ومنعا لتراكب وتداخل الامواج الزلزالية فقد قمنا بنمذجة عناصر ماصة للطاقة . وقمنا بالتعبير عن الفعل المتبادل بين التربة والخزان من خلال نمذجة عناصر تماس خاصة بين سطح التربة وسطح الاساس .ثم اجرينا التحليل الديناميكي للخزان تحت تأثير السجل الزمني لزلزال Elcentroبحالتين فارغ وملئ . بعد ذلك تمت تقوية الجملة الحاملة للخزان من خلال ربط الأعمدة والنواة ببلاطة بيتونية مسلحة سماكتها 15 سم عند مستويين مع الارتفاع , وتم حساب مقادير الاستجابة الديناميكية المتمثلة بالقص القاعدي ,عزم الانقلاب و ازاحة قمة الخزان . ومن ثم اجراء المقارنات بين النتائج لبيان اثر تقوية الجملة الحاملة على قيم الاستجابة الديناميكية للخزان حيث بينَت النتائج أن قيم الاستجابة تنخفض بشكل جدير بالدراسة مقارنة مع النموذج الشائعThe research included the analytical dynamic study of elevated water tank . and study nonlinear dynamic behavior of effect the (water- structure- soil) interaction. its application on a numerical model of a water tank with capacity of 100 cubic meter commonly used prepared from reinforced concrete supported on a frame system using FEM. The tank was modeled by FEM using ABAQUS software. In addition, the soil was modeled using FEM with the modeling of energy absorbent boundary elements (damping elements) to prevent the interaction of seismic waves. The (soil – foundation) interaction was expressed by modeling special interface elements. Then, the dynamic analysis of this system was carried out under the effect of El-Centro time history .Two cases of filling were considered (empty and full container). Parameters of dynamic response of the tank (base shear, bending moment and displacement of the tank) was calculated. Moreover, the frame supporting system was supported by joining the columns and core with a slab with thickness of 15cm located on the height of the holding frame on two levels. Same analysis was carried out with the same parameters on a specific value also for two cases of filling (empty and full container). The results were compared to determine the effect of joining the frame system on the dynamic response of the tank. The results showed that the values of dynamic response of the tank significantly affected by the frame supporting system; the response significantly decreased compared to the common model.